2008
DOI: 10.1161/hypertensionaha.107.101253
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role of Protein Kinase C-δ Tyr 311 Phosphorylation in Vascular Smooth Muscle Cell Hypertrophy by Angiotensin II

Abstract: Abstract-We have shown previously that activation of protein kinase C-␦ (PKC␦) is required for angiotensin II (Ang II)-induced migration of vascular smooth muscle cells (VSMCs). Here, we have hypothesized that PKC␦ phosphorylation at Tyr 311 plays a critical role in VSMC hypertrophy induced by Ang II. Immunoblotting was used to monitor PKC␦ phosphorylation at Tyr 311 , and cell size and protein measurements were used to detect hypertrophy in VSMCs. PKC␦ was rapidly (0.5 to 10.0 minutes) phosphorylated at Tyr 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 64 publications
2
25
0
1
Order By: Relevance
“…PKC␦ is a ubiquitously expressed member of the Ca 2ϩ -independent family of new PKC isoforms implicated in diverse cell functions, including cell proliferation, cell migration, and cell survival (48). The translocation of PKC␦ to the nucleus is critical for cell responses induced by AngII (16,45) and various genotoxins and apoptotic stimuli (48) and relies on a bipartite nuclear localization sequence (NLS) in the PKC␦ protein (60). Although the stabilizing effects of HuR on ARE-bearing mRNA are important for protection of mRNA from cytoplasmic decay by the exosomal complex, HuR binding to target mRNA already occurs in the nucleus (19,32).…”
mentioning
confidence: 99%
“…PKC␦ is a ubiquitously expressed member of the Ca 2ϩ -independent family of new PKC isoforms implicated in diverse cell functions, including cell proliferation, cell migration, and cell survival (48). The translocation of PKC␦ to the nucleus is critical for cell responses induced by AngII (16,45) and various genotoxins and apoptotic stimuli (48) and relies on a bipartite nuclear localization sequence (NLS) in the PKC␦ protein (60). Although the stabilizing effects of HuR on ARE-bearing mRNA are important for protection of mRNA from cytoplasmic decay by the exosomal complex, HuR binding to target mRNA already occurs in the nucleus (19,32).…”
mentioning
confidence: 99%
“…In VSMCs, PKC␦ has been known to be activated upon ANG stimulation leading to AKT activation (38) and PKC has been suggested to play a major role in AT1R-mediated ERK/Elk-1 activation via the Ras/MEK pathway (24). We showed that inhibition of PKC activity using chemical inhibitors or by depletion of its expression by RNAi inhibited G protein-dependent (early time point) AT1R-mediated ERK activation in VSMCs.…”
Section: Discussionmentioning
confidence: 81%
“…Phosphorylation of PKC at Tyr-313 by Src family kinases has also been reported in a variety of cell types in response to non-apoptotic stimuli [117][118][119]46,120,32,121,100]. While some of these studies have shown that phosphorylation at Tyr-313 is required for PKC function, one consequence of Tyr-313 phosphorylation is that it regulates the ability of the enzyme to autophosphorylate its own A-loop and thus fine-tune substrate specificity [32,46].…”
Section: Accepted M Manuscriptmentioning
confidence: 96%